Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1128/aem.02340-21
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Thermal Stress on the Physiology and Bacterial Communities of Two Key Mediterranean Gorgonians

Abstract: In the Mediterranean Sea, the tree-shaped gorgonian corals form large forests that provide a place to live for many species. Because of this important ecological role, it is crucial to understand how common habitat-forming gorgonians, like Eunicella cavolini and Paramuricea clavata , are affected by high seawater temperatures that are expected in the future due to climate change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 76 publications
2
16
0
Order By: Relevance
“…The first involves phenotypic plasticity and long-term acclimation; colonies impacted in 1999 may have been able to acclimate to the extreme warm conditions via phenotypic plasticity (e.g., via downregulating stress response genes such those associated with apoptotic signaling or through upregulation of heat shock proteins 18 , 67 ), and have maintained this “more thermotolerant” phenotype over the years. In gorgonians, such long-term acclimation could also involve shifts of baseline expression of multiple colony genes that assist in coping with oxidative stress 8 , 35 . The long-term persistence of acclimation could contribute to population persistence by gaining time for genetic adaptation to occur 68 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first involves phenotypic plasticity and long-term acclimation; colonies impacted in 1999 may have been able to acclimate to the extreme warm conditions via phenotypic plasticity (e.g., via downregulating stress response genes such those associated with apoptotic signaling or through upregulation of heat shock proteins 18 , 67 ), and have maintained this “more thermotolerant” phenotype over the years. In gorgonians, such long-term acclimation could also involve shifts of baseline expression of multiple colony genes that assist in coping with oxidative stress 8 , 35 . The long-term persistence of acclimation could contribute to population persistence by gaining time for genetic adaptation to occur 68 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous experiments conducted with P. clavata populations sampled before and after the summer (therefore with different nutritional status 29 ), showed that the nutritional status of colonies does not significantly affect thermotolerance when colonies are fed during the experiment 31 , as was the case in our experimental setup. Moreover, the energy reserves of colonies seem to play a very limited role in their thermotolerance when compared with other factors such as their antioxidant capacity 35 . Overall, these data support the higher thermotolerance observed in Lighthouse population as more likely being related to the thermal stress history than to other environmental or physiological factors influencing its energetic reserves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This contrasts with "bleaching" which Bonacolta 5 takes place in zooxanthellate corals and is when the algal symbiont leaves the coral host during periods of high heat-stress. P. clavata is more sensitive to elevated seawater temperatures than other gorgonians, marked by a significant loss in energy reserves, reduced feeding ability, and partial mortality after heat-stress (13). A complete characterization of the P. clavata microbiome before heat-stress can better elucidate the role of the microbiome to overall holobiont health and fitness in the face of warming ocean temperatures.…”
Section: Bonacoltamentioning
confidence: 99%
“… Ziegler et al (2019 ) hypothesized that coral species with low physiological plasticity would have a more stable microbiome, and vice versa. Thermal stress is often associated with an increase in potential pathogens, such as Vibrio ( Morrow et al, 2018 ), and a decrease in potentially beneficial symbionts, such as Endozoicomonas , in both scleractinian corals and octocorals ( McDevitt-Irwin et al, 2017 ; Maher et al, 2020 ; Li et al, 2021 ; Savary et al, 2021 ; Tignat-Perrier et al, 2022 ). Additionally, bacterial virulence or the upregulation of bacterial virulence and secondary metabolism genes are also observed at higher temperatures ( Vega Thurber et al, 2009 ; Littman et al, 2011 ; Kimes et al, 2012 ; Garren et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%